Carbon capture, utilization, and storage (CCUS) technologies: Evaluating the effectiveness of advanced CCUS solutions for reducing CO2 emissions - Enobong Hanson; Chukwuebuka Nwakile; Victor Oluwafolajimi Hammed (Results in Surfaces and Interfaces)
This review provides a comprehensive examination of Carbon Capture, Utilization, and Storage (CCUS) technologies, focusing on their advancements, challenges, and future prospects. It begins with an overview of carbon capture methods, including pre-combustion, post-combustion, and oxy-fuel combustion techniques, highlighting recent technological improvements and associated challenges. The review then explores various carbon utilization strategies, such as chemical conversion, biological processes, and mineralization, discussing emerging technologies, potential applications, and the economic and environmental benefits of utilizing captured CO2. The discussion on carbon storage covers geological options like saline aquifers and depleted oil and gas fields, as well as recent advancements in monitoring and safety measures. The review assesses long-term stability and the risks linked to CO2 storage. In addressing the integration and optimization of CCUS systems, it evaluates the synergies between capture, utilization, and storage, includes techno-economic analyses of integrated systems, and presents case studies of successful CCUS projects. Economic feasibility and scalability are scrutinized through cost analysis, barriers to large-scale implementation, and the role of policy and regulatory frameworks. The review also identifies key research gaps, explores innovation potential, and provides strategic recommendations for advancing CCUS adoption. In conclusion, the findings underscore the essential role of CCUS in mitigating climate change, while highlighting the need for continued innovation, policy support, and cost reductions to enable its widespread deployment and effectiveness.